2015
DOI: 10.1103/physrevb.92.205418
|View full text |Cite
|
Sign up to set email alerts
|

Binding energies of exciton complexes in transition metal dichalcogenide monolayers and effect of dielectric environment

Abstract: Excitons, trions, biexcitons, and exciton-trion complexes in two-dimensional transition metal dichalcogenide sheets of MoS2, MoSe2, MoTe2, WS2 and WSe2 are studied by means of density functional theory and path integral Monte Carlo method in order to accurately account for the particle-particle correlations. In addition, the effect of dielectric environment on the properties of these exciton complexes is studied by modifying the effective interaction potential between particles. Calculated exciton and trion bi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

51
265
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(316 citation statements)
references
References 50 publications
(72 reference statements)
51
265
0
Order By: Relevance
“…1. (Here we use m r =0.20m 0 , which is slightly larger than predicted by theory [19,21]; however this value is consistent with modeling of σ 1s [40] and as shown below is independently recommended by the high-field shifts of the 3s/4s states.) In marked contrast to the 1s state, the quadratic shift of the 2s state is ∼15× larger (σ 2s = 4.6 ± 0.2 µeV/T 2 ), confirming that the 2s exciton has a considerably larger radius r 2s √ 15 r 1s 6.6 nm.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…1. (Here we use m r =0.20m 0 , which is slightly larger than predicted by theory [19,21]; however this value is consistent with modeling of σ 1s [40] and as shown below is independently recommended by the high-field shifts of the 3s/4s states.) In marked contrast to the 1s state, the quadratic shift of the 2s state is ∼15× larger (σ 2s = 4.6 ± 0.2 µeV/T 2 ), confirming that the 2s exciton has a considerably larger radius r 2s √ 15 r 1s 6.6 nm.…”
mentioning
confidence: 87%
“…The very different energy shifts of the 2s, 3s, and 4s excited states of X 0 are observed and studied for the first time. This permits not only their unambiguous identification but also allows for direct quantitative comparison with leading theoretical models based on the non-hydrogenic screened Keldysh potential [19][20][21]. A value of m r is experimentally obtained.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has revealed significant interactions between individual excitons in monolayer TMDs. In particular, two excitons at different valleys can be bound to form an excitonic molecule, the intervalley biexciton, with unusually large binding energies (40−70 meV) [9,10,[26][27][28]. These intervalley biexcitons offer an effective channel to couple the two valleys, with selection rules different from those for single excitons.…”
mentioning
confidence: 99%